Analisis Produktivitas dengan menggunakan Metode American Productivity Center (APC) Pada PT. Florindo Makmur - Walady Utama, Denny; Fiqri Lubis, Yahya; Meuthia Hasibuan, Yetti (SURYA TEKNIKA, 2024)
PT. Florindo Makmur is a company that processes cassava into tapioca flour as a finished product. This company requires productivity measurements to describe the success of a company in utilizing the resources it has to achieve maximum results. This research aims to determine the level of productivity using the American Productivity Center method and carry out further analysis of the results obtained using a fishbone diagram if a decrease in productivity is found. The type of data used in this research is secondary data, where the data obtained is a copy of data that is already owned by the company. The results of this research show that the productivity index decreased by -17.71% from the previous year which was due to a partial decrease in productivity in the input elements of labor and raw materials. The profitability index rose by +1.20%. And the price improvement index increased by +22.97%.